2020
DOI: 10.31196/huvfd.652446
|View full text |Cite
|
Sign up to set email alerts
|

Muhabbet Kuşları ve Kanaryalarda Trachea ve Syrinx’in Makroanatomik ve Histolojik İncelenmesi

Abstract: The purpose of the present study is to examine and compare the trachea and larynx caudalis of budgerigars and canaries in a macroanatomic manner. 18 canaries and 29 budgerigars that were collected as dead from the clinics of the surrounding area were used in this study. The number of cartilago trachea was 46-47 in canaries; and 53-61 in budgerigars. Crossman's Triple Staining Method was used for histological examinations. 0.1% methylene blue solution was used to examine in a stereo microscope. Tracheobronchial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In long-legged buzzard, this number was 89-96; the mean number of cartilaginous rings was 64.2±1.2 in Kingfisher Birds and 151±12 in turkey. We found that the house sparrow had 45-60 cartilaginous rings in their trachea, that agrees with (23) who found 53-61 in budgerigars, 46-47 in canaries and other Passeriformes birds. This also came from species differences and variations in body volume and this result accept with (1) who said that the number of the tracheal rings ranged from about 30 in small passeriform birds to about 350 in long neck flamingos.…”
Section: Discussionsupporting
confidence: 92%
“…In long-legged buzzard, this number was 89-96; the mean number of cartilaginous rings was 64.2±1.2 in Kingfisher Birds and 151±12 in turkey. We found that the house sparrow had 45-60 cartilaginous rings in their trachea, that agrees with (23) who found 53-61 in budgerigars, 46-47 in canaries and other Passeriformes birds. This also came from species differences and variations in body volume and this result accept with (1) who said that the number of the tracheal rings ranged from about 30 in small passeriform birds to about 350 in long neck flamingos.…”
Section: Discussionsupporting
confidence: 92%
“…The syrinx of singing birds is of great importance as it is used in communication between each other and mating (Gaunt & Gaunt, 1977; Goller & Larsen, 1999; Gaban-Lima & Höfling, 2006). In the present study, the syrinx of budgerigar is considered as tracheobronchial in type according to its observed structural characteristics as well as the biological classification of this bird species (Rodríguez & Fabila, 2010; Gündemir & Alpak, 2020). The tracheobronchial syrinx is also recorded in many other bird species such as mallards (Frank et al, 2007; Yilmaz et al, 2012; Mohamed, 2017 b ), geese (Onuk et al, 2010; Mohamed, 2017 a ), turkeys (Arican et al, 2007; Khaksar et al, 2012; Ragab et al, 2016), quails (Bayram & Liman, 2000; Cevik-Demirkan et al, 2007), ostriches (Yildiz et al, 2003), long-legged buzzards (Kabak et al, 2007), Denizli roosters (Taşbaş et al, 1994), guinea fowls (Al-Bishtue, 2014), seagulls (Ince et al, 2012), and eagle owls (Cevik-Demirkan & Ozdemir, 2011).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…3 The chirping variation is a manifestation of the articulation formed by the syrinx cartilage. In previous studies, syrinx organs were morphometrically revealed in pigeons, 4 parakeets and canaries, 5 chickens and rock dove, 6 sparrows 7 and penguins. 8 The syrinx will stimulate the vibrations reflected from each cartilage to produce sound frequency.…”
Section: Introductionmentioning
confidence: 94%
“…This line is emphasized from the end profundal syringeal muscle to the bronchosyringeal-1 cartilage (Figure 1B). 5 For trachea diameter, evaluation was performed on the upper trachea, middle trachea, and lower trachea sides using a vernier caliper (Figure 1C).…”
Section: Syrinx Morphometric Evaluationmentioning
confidence: 99%